2020
DOI: 10.3390/met10111426
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Pure Chalcocite with Reject Brine and MnO2 from Manganese Nodules

Abstract: Chalcocite (Cu2S) has the fastest kinetics of dissolution of Cu in chlorinated media of all copper sulfide minerals. Chalcocite has been identified as having economic interest due to its abundance, although the water necessary for its dissolution is scarce in many regions. In this work, the replacement of fresh water by sea water or by reject brine with high chloride content from desalination plants is analyzed. Additionally, the effect of adding MnO2 from available manganese nodules in vast quantities at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Studies have shown that the leaching of caliche using reject brine is technically feasible and delivers similar results than using seawater (Ordóñez et al 2015(Ordóñez et al , 2017. In another study, the use of reject brine in the leaching of pure chalcocite provides better results than the use of seawater (Torres et al 2020).…”
Section: Repurpose (R6)mentioning
confidence: 98%
“…Studies have shown that the leaching of caliche using reject brine is technically feasible and delivers similar results than using seawater (Ordóñez et al 2015(Ordóñez et al , 2017. In another study, the use of reject brine in the leaching of pure chalcocite provides better results than the use of seawater (Torres et al 2020).…”
Section: Repurpose (R6)mentioning
confidence: 98%
“…( 2) could be rewritten to include both dependences of the reaction. Then, considering the evident proportional relation between the copper recovery from secondary sulfides and chloride concentration [20,26,27,62,63], the term   is incorporated into the analytical model as factors of both scales, as shown in Equations ( 5) and ( 6). The term   i (chloride concentration, cCl) is defined as the potency of the fraction of the sampled chloride concentration (xi) over the average concentration (x) raised to a mathematical adjustment constant i, where i are the particle levels and heap height.…”
Section: Analytical Models For Heap Leachingmentioning
confidence: 99%
“…Chile is the largest copper producer worldwide, with a 27.9% share [2][3][4] of production and 29% of the reserves of this commodity [5]. Copper oxides processed by hydrometallurgy are becoming increasingly scarce in Chile (from 30.8% in 2015 to 12% in 2027), while copper sulphides are being found in more significant amounts [6][7][8]. The National Service of Geology and Mining [2] (SERNAGEOMIN, by his acronym in Spanish) has indicated that 39.2% of copper production takes place through hydrometallurgical processes, but most of the production (60.8%) takes place through flotation processes.…”
Section: Introductionmentioning
confidence: 99%